Vom Reststoff zum hochtechnischen Spritzgießkunststoff - Recyclingtechnologie für thermoplastische endlosfaserverstärkte Kunststoffe - Moritzer, Elmar; Heiderich, G. (Ingenieurspiegel - Fachmagazin für Ingenieure)

WPC: Compoundierung und Rezepturen - Schöppner, Volker; Böhm, N.; Reinders, F. (WAK-Symposium)

Entwicklung des Herstellprozesses von eigenverstärktem Polycarbonat durch monoaxiales Recken - Wibbeke, Andrea

Prozessoptimierung und Evaluierung der in-situ Bildung von nanoskaligen Cellulosefasern in SBR - Zabel, Mathias

Herstellung komplexer polymerer Hohlkörperstrukturen - Plugge, Thorsten

Theoretische und experimentelle Betrachtung schnelllaufender Einschneckenextruder - Hörmann, Heinrich

Untersuchung des instationären Verhaltens an einem Einschneckenextruder - Korsmeier, André

Finishing of ABS-M30 Parts Manufactured with Fused Deposition Modeling with Focus on Dimensional Accuracy - Fischer, M.; Schöppner, Volker (25th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) parts are prone to process-related rough and wavy surfaces with stair-stepping effects whenever the parts produced have sloped or rounded geometries. These stair-stepping effects can be reduced by using a smaller slice height, but complete elimination is not possible. In this paper, FDM parts manufactured with the material ABS-M30 are finished using mass finishing methods. The mass finishing is done with a trough vibrator, which is comparatively gentle to the parts in comparison to other mass finishing technologies. The analysis discusses the surface-smoothing effect of finishing time and intensity on various part sizes and build orientations. In addition, the dimensional accuracy of the parts after the finishing process is examined.

Effects of a mass finishing process on parts produced from Ultem 9085 by Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (ANTEC)
Parts produced by Fused Deposition Modeling (FDM) tend to have rough and undulating surfaces with staircase effects on rounded and slanting areas of the part. This is due to the characteristics of the process. In many fields of application, high demands are made on the optical quality of the part. An improvement in the surface quality of FDM parts made of Ultem*9085 can be achieved through post-treatment with a mass finishing process. In this paper, FDM specimens are post-treated in a disk finishing unit. Influences of the mass finishing process are analyzed with regard to the dependence of surface quality on the various process parameters and on the finishing medium, grinding time and grinding speed. The finishing efficiency depends on the finishing media and decreases for lower finishing time. For all media a lower disk velocity results a smaller grinding effect, but there are clearly differences between the finishing media. The paper also discusses effects of the grinding process on the mechanical properties of the parts. Especially small part geometries and parts build in z-direction tend to break during the finishing process.

Mechanical Analysis of Lightweight Constructions manufactured with Fused Deposition Modeling - Bagsik, A.; Josupeit, S.; Schöppner, Volker; Klemp, E. (29th International Conference of the Polymer Processing Society)
Additive production techniques have the advantage of manufacturing parts without needing a forming tool. One of the most used additive manufacturing processes is "Fused Deposition Modeling" (FDM) which allows the production of prototypes and end-use parts. Due to the manufacture layer by layer, also complex part geometries can be created in one working step. Furthermore, lightweight parts with specific inner core structures can be manufactured in order to achieve good weightrelated strength properties. In this paper the mechanical behavior of lightweight parts manufactured with the 3D production system Fortus 400mc from Stratasys and the material Polyetherimide (PEI) with the trade name Ultem*9085 is analyzed. The test specimens were built up with different inner structures and building directions. Therefore, test specimens with known lightweight core geometries (e.g. corrugated and honeycomb cores) were designed. A four-point bending test was conducted to analyze the strength properties as well as the weight-related strength properties. Additionally the influence of the structure width, the structure wall thickness and the top layer thickness was analyzed using a honeycomb structure.

Verfahrenstechnische Entwicklung zum Hinterspritzen von Echtholzfurnieren mit Wood-Plastic-Composites (WPC) - Schröder , Cathrin

Untersuchung des Prozessverhaltens neuartiger Einzugzonen-Konzepte für Kautschukextruder - Hallmann, Tobias

Some Investigations Regarding the Surface Treatment of Ultem 9085 Parts Manufactured with Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (24th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) parts are typically subject to process-related rough or wavy surfaces, with stair-stepping effects whenever the parts produced have sloped or rounded part geometries; however, the level of optical quality frequently required demands that parts feature a smooth surface. In this paper, the results of a high-energy finishing process, which uses a disc finishing unit and is designed for parts manufactured with the material Ultem*9085, are presented. The analysis discusses the surface-smoothing effect of various finishing materials with varying geometries, as well as the effect of finishing time and speed. Additionally, the efficiency of the surface treatment has been analyzed specifically at corners, edges and in cavities.

Long-Term ageing effects on Fused Deposition Modeling Parts manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (23rd Annual International Solid Freeform Fabrication Symposium)
Relating to the direct manufacturing of end-use parts the knowledge about the effect of the long-term ageing of Fused Deposition Modeling (FDM) parts is of particular importance. For this, tensile specimens were stored for time periods of up to 52 weeks in two different conditions and the testing was conducted at different temperatures within a temperature range of -60°C to +160°C. Further tests were made after the exposure in multiple media. The parts were built up with the system “Fortus 400mc” from Stratasys with the material Ultem*9085 in two different build directions, the strongest direction X (on its side) and the weakest build direction Z (upright) and with the standard toolpath parameters of the Insight software version 7.0.

Tensile and Flexural Properties of Fused Deposition Modeling Parts Manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (1st International Conference on Thermo-Mechanically Graded Materials)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is "Fused Deposition Modeling" (FDM). It is one of the most used additive manufacturing processes to produce prototypes and end-use parts. From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer with a particular tool path. Due to the thermal fusion the material bonds with the layer beneath and solidifies. Thus a permanent bonding of two layers is formed. In this paper the mechanical data of parts, manufactured with the system Fortus 400mc from Stratasys with the material Ultem*9085 are presented. Tensile and flexural tests according to both, the ASTM and the ISO standard, are conducted. Test specimens are generated with the standard parameters of the native software in different build directions. The tests show different strength and strain characteristics that depend on the given structure as a result of the build direction. Furthermore tensile specimens according to the ASTM standard are generated with changed parameters of the native software to increase the mechanical strength properties. The results are compared to injection molded strength properties.

Extensive Analysis of the mechanical strength properties of Fused Deposition Modeling Parts manufactured with ULTEM 9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (5th International Conference on Polymer and Mould Innovations)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is “Fused Deposition Modeling” (FDM). It is one of the most used additive manufacturing processes to produce prototypes and end-use parts. From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer with a particular tool path. In this paper the mechanical data of parts, manufactured with the system Fortus 400mc from Stratasys with the material Ultem*9085 are presented. Tensile specimens are generated with the standard parameters as well as with changed parameters of the native software to analyze the influence of these parameters on the mechanical strength properties. The tensile tests show different strength and strain characteristics that depend on the given structure and as a result of the build direction. Furthermore the toolpath parameters have an effect on the strength characteristics and the break behavior. In addition, tensile specimens are tested under the influence of different temperatures and after a thermal cycling.

Mechanical Properties of Fused Deposition Modeling Parts Manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker (ANTEC)
In this work the influence of the orientation and the toolpath generation of manufactured parts based on the mechanical data are analyzed. Tensile Specimen are generated with the given parameters as well as with changing parameters of the native software based upon the CAD data. The parts then are built up with the “Fortus 400mc” from Stratasys. First tensile tests show different strength and strain characteristics that depend on the given structure and as a result of the build direction. The influence of the parameters was analyzed with a statistic test method by using the software Design Expert.

Simulating Tightly Intermeshing, Co-Rotating Twin Screw Extruders with SIGMA - Kretzschmar, Nils; Schöppner, Volker (Proceedings of the 2010 Summer Computer Simulation Conference)
A large proportion of plastics today is compounded, which means the process from refining a raw material to the processable material. For this process compounding extruders are used which mostly involve tightly intermeshing, co-rotating twin screw extruders. These extruders consist of two closely spaced screws which rotate in the same direction and convey the raw material to the screw tip. These screws are surrounded by several barrel modules which heat or cool the material. As the whole design of the machine is modularly arranged the process behavior of a twin screw extruder depends for the main part on the arrangement of the screw and the barrel elements. Until today this arrangement and process optimization is conducted by experienced engineers and with the help of trial-and-error methods. Furthermore, theoretical models are used with which the behavior of the extruder is estimated. As these models are mostly very complex they are only made available with the realization in different software projects. One of the tools is called SIGMA. Within this paper SIGMA is introduced as a software to optimize a twin screw extruder. SIGMA supports the engineer already in the early stages of the extruder arrangement.
Keywords: process optimization; polymer engineering; compounding; twin screw extruder; simulation

FDM Part Quality Manufactured with ULTEM 9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (Proceedings of International Conference Polymeric Materials)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is “Fused Deposition Modeling” (FDM). From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material in only a few working steps. Native software automatically slices the data, calculates the support structures, and creates toolpaths. The parts then are built up layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer. This technology began as a process for creating prototype parts; recently it has found new utility in the production of manufacturing tools and as a manufacturing process for end-use parts. In order to be used as a part for serial production, the components must possess the required mechanical properties. To this end, not only is the chosen material relevant, but a correct process control is also necessary. An interesting material for the aircraft and automotive industry is the material PEI with the trade name Ultem*9085. This material should typically be used on FDM-machines for the manufacturing of end products. The aim of the research is to determine the present mechanical data based on the process control, as well as reproducibility from job to job. In this work the influence of the orientation and the structure of the manufactured parts based on the mechanical data are analyzed. Sample parts are generated with the given parameters of the native software based upon the CAD data. First, specimens were analyzed concerning their geometry and configuration. The dimensions and weight were measured. The mechanical tests conducted were the tensile and compression tests.